Epidemiological Investigation of A Goat Rabies Outbreak and Assessment of Knowledge, Attitudes, and Practices of Communities Regarding Rabies in the Rural Commune of Sabou, Burkina Faso - Madi Savadogo; Guy Sidwatta Ilboudo; Laibané Dieudonné Dahourou; Hamidou Zangré; Kalidou Zerbo; Abdoul Kader Ilboudo; Zékiba Tarnagda (Journal of Epidemiology and Public Health, 2024)
Background: Dog-mediated human rabies is one of the top five priority zoonotic diseases identified for the One Health multisectoral engagement in Burkina Faso. Integrated approaches are required in endemic areas for reliable data collection and improved management of bite victims. This study aimed to assess the knowledge, attitudes, and practices of communities regarding rabies and preventive methods.Subjects and Method: A cross-sectional household survey was conducted in the Commune of Sabou after a goat rabies confirmation. A structured questionnaire was administered to 305 house-hold members to capture data. The dependent variables in this study were the knowledge of rabies and animal vectors, the action to be taken regarding the biting animal, the main challenges to PEP coverage, the knowledge of preventive measures, and the minimum age recommended for primo-vaccination. The independent variables in this study were gender, level of education, professional status, and dog-owning status. The study was analyzed using the Chi-Square test.Results: The results provided that the suspected goat was infected by the rabies virus. Subsequently, the outbreak joint investigation initiated involved key local stakeholders. Data collected during the investigation raised the need for counter-measures such as identification of awareness gaps, organization of a dog rabies vaccination, and awareness-raising campaigns in the local communities. The household survey revealed low awareness about animals involved in human rabies transmission, the common routes of transmission, and the postexposure prophylaxis. Moreover, hindrances to postexposure prophylaxis access cited by the participants were related to frequent vaccine shortage (39.7%) as well as financial inaccessibility (60.3%). In addition, 40% of participants were not well aware of pet rabies prevention and reported only 67.6% of owned dogs were vaccinated.Conclusion: According to the study results, there is a need to strengthen rabies surveillance, promoting outbreak joint investigation, and integrated bite case management. Moreover, key messages on animal and human rabies prevention should be developed and shared with the communities. Keywords: Canine rabies, zoonoses, joint investigation, community awareness, public health, household survey